Catolicismo midiático, juventude e testemunho: uma análise do programa PHN da TV Canção Nova - Ferreira, Virginia Diniz (2018)
The evolution of media society to mediatized society has made that sense practices alter the ways of establishing social practices (FAUSTO NETO, 2008). Thus, the religious field alters its modes of functioning in function of mediatic logics (Borelli, 2010a) and mediatic Catholicism is perceived as a phenomenon, in the mediatic appropriation made by the charismatic movement. Among the Catholic broadcasters, TV Canção Nova (CN) stands out for the technological aport and investment in platforms and media. It integrates this context of alteration of religious practices, due to the transformation generated by being present in the events that populate the process of mediatization of society (FLORES, 2010; GASPARETTO, 2009) and carries out the propagation of religious discourse, from the media. This reasearch addresses the process of mediatization of society (VERÓN, 1997) and its implications over media practices performed by Catholic charismatic broadcasters, which emerge from mediatic Catholicism (CARRANZA, 2011). This way, problematizes: how the PHN (Por Hoje Não Vou mais Pecar) use the strategies of addressing mode to target the young public and lead to a possible adhesion to the faith? A qualitative, descriptive and interpretive research is carried out, divided into three phases: First, the choice of the corpus, in the transmitter of the programs on YouTube, Canção Nova Play, with 70 issues, from 02/02/2016 to 10/03/2017. As a complementary strategy, a participatory observation was made during the production and recording of the program, held on 06/30/2017, on TV CN, which helped identify the content preferred by the public, consumed media and PHN public profile. In the second phase, five programs were chosen, following the criteria of presenters (official and substitutes) and scenarios (external and studio); the topics covered by the program were categorized and the selection of the exhibition of the five editions for final analysis, referring to the days: 12/01/2016; 2/16/2016; 04/16/2016; 8/30/2016 and 9/20/2016. In the third and last phase, the analysis of the addressing modes (GOMES I., 2011) was carried out to reach the objectives and answer the questions: how the program is structured, what strategies are used by the production to retain and capture the public young faithful and what type of faithful is constituted from the program. The study evidences that the testimony (PUNTEL, 2005) is the structural basis of the program and serves as a contact strategy (FAUSTO NETO, 2004) for the proposal of adherence of the faith to young people, emerging in the language of charismatic mediatic Catholicism.